The Homosexuality Debate in Malawi - Mawerenga, Jones Hamburu (Mzuni books, 2018)
Homosexuality is a cross-cutting challenge to Malawian society with theological, socio-cultural, economic, legal, political, and human rights implications. This book argues that the solution to the homosexuality debate in Malawi does not lie in either the criminalization or decriminalization of homosexuality; neither does it lie in homophobia nor heterophobia. However, the solution to the homosexuality debate lies in achieving a harmonious co-sexistence of both heterosexuals and homosexuals by practicing mutual tolerance. The book concludes by suggesting various activities to be taken by: The Government of Malawi; Gay Rights Activists; Religious Leaders; Traditional Leaders; and Malawian Society to ensure the aforementioned tolerance and understanding is encouraged